Antioxidative potential of propolis on Staphylococcus aureus infected BALB/c mice: A biochemical study (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Drug resistance, according to World Health Organization, is one of the most serious threats to public health. This makes antibiotics ineffective and reduces their therapeutic potential. One of the most prevalent multidrug-resistant bacteria is Staphylococcus aureus which is considered to be the most common pathogen and mortality factor in both hospital and non-hospital environments worldwide. Due to an unprecedented increase in reports of drug resistance in pathogens, and also due to adverse and severe side effects of drugs, there is an urgent need to redirect scientific efforts towards search for anti-oxidative natural substances and other alternative sources having therapeutic potential against microbes. Natural products such as propolis seem to exhibit most promising therapeutic potential against microorganisms. Thus, present study is focused on antioxidative potential of propolis in combination with standard antibiotics ampicillin and amoxicillin against S. aureus infected BALB/c mice. For this, mice were divided into seven groups, they were decapitated after suitable experimental periods, then their liver, kidney and spleen were excised from control and experimental groups, which were homogenized and then used for different biochemical estimations following the standard protocols. Results showed that S. aureus caused severe biochemical alterations by 5th day of infection that is, lipid peroxidation increased significantly (P